Development of E-Learning based Remedial Videos on Fractions in Middle School - Johar, Rahmah; Moulina, Aisyah Rayhan; Mailizar; Lestari, Mulia; Away, Yuwaldi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The Covid-19 pandemic has opened the gates to digital learning in mathematics education and increased the use of online learning. However, teachers still rare to use digital technology as feedback and final evaluation of students. Therefore, an e-learning based remedial video is needed to developed. The research aims to produce e-learning based remedial videos on fraction that meet the criteria of valid, practical and effective. This research is development research with ADDIE models namely analysis, design, development, implementation, and evaluation. The subjects of this research were class 8 students at junior high school from three school levels in Banda Aceh, Indonesia. Data was collected using video validation sheets, students’ response questionnaires, and remedial tests. The results show that e-learning based remedial videos was valid based on expert judgements, practical because students gave positive responses and effective because N-Gain of the percentage of students reached the Minimum Completeness Criteria (MCC) on diagnostic test and remedial test was 0.5 on the medium category.